Gene Expression Profiling of Human Monocyte-derived Dendritic Cells – Searching for Molecular Regulators of Tolerogenicity - Schinnerling, Katina; García-González, Paulina; Aguillón, Juan Carlos (Frontiers in Immunology, 2015)
The ability of dendritic cells (DCs) to initiate and modulate antigen-specific immune responses has made them attractive targets for immunotherapy. Since DC research in humans is limited by the scarcity of DC populations in the blood circulation, most of our knowledge about DC biology and function has been obtained in vitro from monocyte-derived DCs (moDCs), which can be readily generated in sufficient numbers and are able to differentiate into distinct functional subsets depending on the nature of stimulus. In particular, moDCs with tolerogenic properties (tolDCs) possess great therapeutic potential for the treatment of autoimmune diseases. Several protocols have been developed to generate tolDCs in vitro, able to reinstruct auto-reactive T cells and to promote regulatory cells. While ligands and soluble mediators, by which DCs shape immune responses, have been vastly studied, the intracellular pathways and transcriptional regulators that govern tolDC differentiation and function are poorly understood. Whole-genome microarrays and proteomics provide useful strategies to dissect the complex molecular processes that promote tolerogenicity. Only few attempts have been made to understand tolDC biology through a global view on ‘omics’ profiles. So far, the identification of a common regulator of tolerogenicity has been hampered by the fact that each protocol, used for tolDC generation, targets distinct signaling pathways. Here we review the progress in understanding the transcriptional regulation of moDC differentiation, with a special focus on tolDCs, and highlight candidate molecules that might be associated with DC tolerogenicity.